Peranan Warna dalam Karya Fotografi - Agnes Paulina Gunawan (Bina Nusantara University, 2012)
In the photographic development, the existence of color as part of the supporting aspect in the art of photography, is definitely influencing the final work of a photographer - whether it is a theory of color as lighting, or color as part of a pigment or chemical compound as part of physique from an object. Choosing a photo object based on colors can also create a meaning or theme in a composition of picture. This is the same when photo shoot is done with lighting that contends specific character or qualities of colors. For example, the use of color gel on the lights can create a condition that will be different when pictures are taken with white lights. Colors in photography can also give an expression or show an emotion visually that the photographer is trying to convey. With that said, a photographer who understands color concept can fix or anticipate any unwanted condition using a filter, for example, when lighting is contaminated with colors which changes the effect from the original color of an object. Therefore, with a thorough knowledge about colors, one can maximize the work just by making use of the available color aspect as part of the art work.